INTERFERENSI LEKSIKAL BAHASA MELAYU JAMBI DALAM PENGGUNAAN BAHASA INDONESIA LISAN - AMRAL, SAINIL (JURNAL PENDIDIKAN BAHASA DAN SASTRA, 2011)
This article is based on the results of the Mini Research by topic; Interference lexicase Jambi Malay Indonesian Use of Oral (Descriptive-Analytic Study of Environmental Conversation Students in Public Elementary School 47 Jambi City). The study focused on lexical interference Jambi Malay to Indonesian spoken in conversation communicating students in four situations, namely: in the teaching-learning process, while playing with peers, communicating with parents and teachers in the school environment, and when communicating with officers schools and parents within the school environment. Data taken by direct observation of events between students conversation, students and parents, students and teachers, and students and school officials at environment State Primary School No. 47 City of Jambi. The aim is to describe the forms of lexical interference, mixed code, and transfer of student speech codes in the context of the above four. Once the data is described based on observations/student observation and recording conversations, for grouped data ferifikated and then analyzed using Miles and Huberman technical. The results show that, more informal context of communication the more likely the occurrence of interference. Elementary School Students 47 City of Jambi set in B1 regional languages do more lexical interference in official and unofficial conversations. Lexical interference that occurs more dominant in the change of the vowels / a / to the vowel sound / o / which lies at the end of the word.Keywords: lexical interference, Jambi Malay, Indonesian language spoken